2022
DOI: 10.1021/acs.jmedchem.2c00172
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Progenitor Kinase 1 in Tumor Immunology: A Medicinal Chemistry Perspective

Abstract: Hematopoietic progenitor kinase 1 (HPK1), a hematopoietic cell-restricted member of the serine/threonine Ste20-related protein kinases, is a negative regulator of the T cell receptor, B cell receptor, and dendritic cells. Loss of HPK1 kinase function increases cytokine secretion and enhances T cell signaling, virus clearance, and tumor growth inhibition. Therefore, HPK1 is considered a promising target for tumor immunotherapy. Several HPK1 inhibitors have been reported to regulate T cell function. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 106 publications
0
21
0
Order By: Relevance
“…At the initiation of this work, there were few literature-reported compounds with activity against HPK1; 12 however in recent years, there has been an explosion of research around the design of HPK1 inhibitors. 13 Even with a large number of efforts in both academia and industry, an FDA-approved HPK1 inhibitor is yet to be realized. In the context of our efforts, exquisite selectivity was desired for achieving an HPK1-driven functional response in cell lines of interest, as there are many kinases involved in leukocyte signaling pathways which, if inhibited, result in immune suppression.…”
Section: ■ Introductionmentioning
confidence: 99%
“…At the initiation of this work, there were few literature-reported compounds with activity against HPK1; 12 however in recent years, there has been an explosion of research around the design of HPK1 inhibitors. 13 Even with a large number of efforts in both academia and industry, an FDA-approved HPK1 inhibitor is yet to be realized. In the context of our efforts, exquisite selectivity was desired for achieving an HPK1-driven functional response in cell lines of interest, as there are many kinases involved in leukocyte signaling pathways which, if inhibited, result in immune suppression.…”
Section: ■ Introductionmentioning
confidence: 99%
“…HPK1 and GLK (MAP4K3) are phylogenetically close and structurally similar members of the MAP4K family, sharing high homology and similarity in sequences and structures . However, GLK opposes the effect of HPK1 on T-cell signaling, as GLK is a positive regulator of T-cell activation/autoimmune responses, , it is a great challenge to design highly selective small molecule inhibitors of HPK1 and retain other kinases that are essential for maintaining intracellular homeostasis and general signal transduction processes due to the certain sequence similarity in the catalytic domain of MAP4K family kinases. , This suggested that achieving selectivity over GLK will be a key challenge for any small molecule HPK1 inhibitor when evaluating the clinical potential . To date, although a number of small-molecule HPK1 inhibitors that exhibit excellent inhibitory activity have been discovered (Figure ), the poor GLK selectivity profile, metabolic stability, permeability, and PK profile limit the further development as clinical candidates, , and no HPK1 inhibitor has been approved in clinical trials yet.…”
Section: Introductionmentioning
confidence: 99%
“…20 Given the compelling evidence, it has been proposed that HPK1 is a highly desirable target in cancer immunotherapy. 21,22 HPK1 and GLK (MAP4K3) are phylogenetically close and structurally similar members of the MAP4K family, sharing high homology and similarity in sequences and structures. 20 However, GLK opposes the effect of HPK1 on T-cell signaling, as GLK is a positive regulator of T-cell activation/autoimmune responses, 23,24 it is a great challenge to design highly selective small molecule inhibitors of HPK1 and retain other kinases that are essential for maintaining intracellular homeostasis and general signal transduction processes due to the certain sequence similarity in the catalytic domain of MAP4K family kinases.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies with single-point kinase active-site mutants have shown that the promising results with knockout mice can be recapitulated by inhibiting kinase activity, suggesting that a small-molecule ATP-competitive approach to HPK1 inhibition could lead to effective immune activation. Intrigued by the possibilities of HPK1 blockade, we and others initiated a program to develop small-molecule ATP-competitive inhibitors of HPK1.…”
mentioning
confidence: 99%